Influence of strontium and niobium on the physical and biological performance of hydroxyapatite as a bioactive coating on implant materials. Issue 22 (15th November 2022) - Panda, Sikta; Bharadwaj, Tanmay; Verma, Devendra; Biswas, Chandan Kumar; Paul, Subhankar
Abstract: The coating of hydroxyapatite (HAP) on the surface of bio-inert metallic implants to augment their bioactivity is in use for the last two decades. Substitution of various materials in HAP further improves the functionality of these coatings. We demonstrate coating of Ti6Al4V alloy sheets with strontium and niobium reinforced HAP using microwave (MW) irradiation technique. Physical characterization revealed, uniform semicrystalline hydroxyapatite coating with enhanced surface roughness and microhardness. The increased surface roughness was accompanied by higher wettability and more protein adsorption. Electrochemical corrosion assessment showed a dramatic increase in corrosion potential and a noticeable decline in corrosion current density suggesting an enhanced anticorrosive behaviour. These implants also exhibited improved hemocompatibility and bacteriostatic properties. Cell viability and confocal microscopy studies of the coated samples showed enhanced cell attachment on the surface. We propose microwave irradiation as a fast and hassle-free alternative for one-pot synthesis and deposition of ionic substituted HAP on metallic implants.